Effect of freezing, osmodehydro-freezing, freezedrying and osmodehydro-freezedrying on the physicochemical and nutritional properties of arazá (Eugenia stipitata McVaugh) - Reyes Álvarez, Camilo Andrés (2023)
Arazá, a berry rich in heat-sensitive bioactives (phenolics/carotenoids/flavonoids/ascorbic acid), may be suitable for preparing functional foods, however, its high perishability hinders its industrial application. Although freezing (Fr) and freezedrying (LIO) are popular methods for preserving fruits, they may cause undesirable quality changes. Adding an osmo-dehydration pretreatment (OD) before freezing (osmodehydro-freezing/OD-Fr) or freezedrying (osmodehydro-freezedrying/OD-LIO) diminishes processing time which may improve the final product quality This study analyzed the effect of Fr/LIO/OD/OD-Fr/OD-LIO on color, antioxidant content/activity, polyphenol composition and bioaccessibility (BAC) of arazá. OD pretreatment increased freezing rate (58 %) and reduced osmodehydro-frozen arazá drip-loss (40%) Osmodehydrated samples presented the highest discoloration levels (15.7), freezing/freezedrying pretreated arazá improved them 16–48 %. Fr/LIO gave the best results regarding polyphenol content (99–48 %), and activity (97–88 %) retention; whereas OD/LIO produced the highest losses (59–84 %). Results showed that in comparison with untreated fruit, freezing arazá did not affect the bioaccessible antioxidants content/activity, conversely, freezedrying reduced antioxidant activity and total-flavonoids BAC levels (14–21 %) without modifying polyphenols/carotenoids bioaccessibilities. Although osmodehydro-freezing increased total-polyphenol bioaccessibility (22 %) without affecting that corresponding to total-flavonoids, it reduced antioxidant activity retention (16–42 %). Osmodehydro-freezdrying impact was negative on all properties (13–55 %) except Ferric-Reducing-Antioxidant-Power that increased (10 %).